Avaliação da efetividade do programa de mindfulness-based relapse prevention (MBRP) como estratégia adjunta ao tratamento da dependência de tabaco - Souza, Isabel Cristina Weiss de [UNIFESP] (2016)
In spite of the relative effectiveness of behavioral and pharmacological treatments, the great majority of smokers are likely to relapse after attempts to quit smoking. The emotional and behavioral regulation following such cessation seem to be risk factors for relapse, which makes it necessary for researchers to come up with therapeutic models that stimulate response to negative affects. The Mindfulness-Based Relapse Prevention program as an adjunct treatment for substance abuse has presented promising results in this regard. However, it has not yet been tested for smoking. The main objective of this dissertation was to evaluate the Mindfulness-Based Relapse Prevention program as an adjunct to the treatment for smoking cessation promoted by the Ministry of Health through the Instituto Nacional de Câncer (National Institute of Cancer) in Brazil. The dissertation is divided into three studies, the first one being a systematic literature review in order to investigate the state of art of clinical trials already published which were based on mindfulness as the main treatment or as an adjunct for the treatment of nicotine dependence (Study 1). The second one is a cross-sectional study to evaluate the factors associated with dispositional mindfulness among smokers who searched for treatment for the first time (Study 2). Study 3 aimed at evaluating the effectiveness and feasibility of Mindfulness-Based Relapse Prevention as an adjunct to the standard treatment for smoking cessation. In study 1 we selected 13 controlled clinical trials out of the 198 articles collected for analysis. The articles reported promising preliminary results in relation to cessation, relapse prevention, reduction in the number of cigarettes smoked as well as mindfulness moderation in the association between craving and smoking. On the other hand, they clearly pointed to the need for better designed clinical trials of mindfulness-based interventions concerning sample size, control group and well described protocols. Study 2 comprised 116 patients who were in a waiting list for treatment of tobacco dependence for the first time. We used the scales Fagerstrom Test for Nicotine Dependence, Hospital Anxiety and Depression Scale, Five Facet Mindfulness Questionnaire-BR and The Positive and Negative Affect Schedule. Descriptive analyses were performed to characterize the sample, after which we used Pearson?s bi-variate correlation analyses between the variable outcome (dispositional mindfulness) and each explanatory variable: anxiety, depression, positive affect, negative affect and the level of tobacco dependence. The linear regression model was adopted to evaluate the contribution of each variable when controlled by the others. The results of the final regression model indicated that 36,2% variance in the levels of dispositional mindfulness of the sample could be accounted for by the positive affects (B = 0.81; p < 0.001), level of tobacco dependence (B = 1.48; p = 0.007) and negative affects (B = -0.44; p = 0.02). Depression and anxiety were not included in the final model (p > 0.10). Study 2 confirmed the association between dispositional mindfulness, levels of tobacco dependence, and positive and negative affects among individuals who search for treatment for the first time. Study 3 presents the results of a pragmatic pilot randomized study comparing patients who had eight sessions of Mindfulness-Based Relapse Prevention in addition to the standard treatment established by the Ministry of Health in Brazil, which follows the principles of relapse prevention, to patients who received only relapse prevention. Eighty-six smokers were randomly assigned to a Mindfulness-Based Relapse Prevention group (n = 44) and an active control of relapse prevention group (n = 42). Data were collected at baseline, pre-intervention, post-intervention and at a 6-month follow-up. They took into account abstinence (Fagerstrom Test for Nicotine Dependence and CO level measured by Smokerlyser); anxiety and depression (Hospital Anxiety and Depression Scale), craving (Questionnaire on Smoking Urges); mindfulness levels (Five Facet Mindfulness Questionnaire), and positive and negative affects (The Positive and Negative Affect Schedule). We performed the descriptive analyses through the presentation of proportion measures, central tendency and dispersion. In order to evaluate the difference between groups we used Fisher?s exact test, Student?s T test and McNemar?s exact test. We also adopted the intention to treat (Intention-To-Treat) due to the high dropout rate. Additionally, we evaluated the ration between the number of abstinent patients in each group and the patients who were still smoking six months after the initial evaluation. The ANOVA for repeated measures was used in the analysis of secondary outcomes. There was no statistically significant difference between the Mindfulness-Based Relapse Prevention and the active control group as regards abstinence after six months. However, in the analysis among participants the Mindfulness-Based Relapse Prevention group presented a tendency to advantage in that period concerning the evolution of abstinence rates (McNemar's 2 = 3.27, df = 1, p = 0.07), since for each abstinent patient only one relapsed, while in the active control group three patients relapsed for each abstinent one (McNemar's 2 = 19.05, df = 1, p = 0.005). As for secondary outcomes, the Mindfulness-Based Relapse Prevention group also showed a tendency towards the reduction of craving (M = 17.583; 95% IC (4.537 | 30.629); p = 0.01), with increase in the levels of mindfulness (M = -7.833; 95% IC (-14.065 | -1.601); p = 0.016) when we compared pre- and post-intervention. This study shows the benefits of Mindfulness-Based Relapse Prevention as an adjunct to the standard treatment for smoking cessation.